History of coastal-marine research in Bahía Culebra, North Pacific, Guanacaste, Costa Rica - Cortés, Jorge (2012)
Bahía Culebra (Culebra Bay) is located on the north Pacific coast of Costa Rica in a seasonal upwelling area. In this paper I present the history of marine research at Bahía Culebra, to summarize what is known and to point out research that should be carried out. Marine organisms of the Bay have been studied since the 1920’s and very intensely during the 1930’s, with the Alan Hancock Pacific Expeditions and the New York Society Zoological Expeditions. Most marine research has been done since 1980 by the Marine Science and Limnology Reseach Center (Centro de Investigación en Ciencias del Mar y Limnología, CIMAR) at the University of Costa Rica. The best studied systems are the coral communities and reefs, followed by zooplankton research. In a compilation of published records of marine organisms 577 are reported and in this Special Issue 20 more are added, for a total of 597 marine species. Even so, more research is needed in several ecosystems and groups. It is necessary and important to develop managment plans to protect and conserve the marine ecosystems and biodiversity of Bahía Culebra.